2018
DOI: 10.1016/j.jrras.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of natural radioactive and heavy metals concentration in underground water

Abstract: Concentrations of natural nuclides (226 Ra, 232 Th and 4 K) and some heavy metals (Cu, Fe. Ni, Pb and As) were measured in groundwater collected from different locations in Makkah region in Saudi Arabia. In the radioactivity measurement, a high purity germanium detector system was used. In addition, chemical analysis was performed by an Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The average measured activity concentrations of the nuclides 238 U, 232 Th and 4 K were 0.558, 0.204 and 4.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…This risk is much lower than the limit 8.4 × 10 −3 , if the total natural radiation dose of 2.4 mSv/y as given by UNSCEAR 2000UNSCEAR (2000. Th average value (0.16 Bq•L −1 ) is almost matched with Saudi Arabia (Alseroury et al, 2018), higher than Jordan (Al-Shboul et al, 2017) and lower than other countries. The present results show that the average of 40 K concentration is nearly matching the value of Nigeria (Ajayi & Owolabi, 2007), higher than Yemen (Abdurabu et al, 2016) and Jordan (Al-Shboul et al, 2017), while it is lower than the other observed values.…”
Section: Lifetime Risk Assessment (R)mentioning
confidence: 73%
“…This risk is much lower than the limit 8.4 × 10 −3 , if the total natural radiation dose of 2.4 mSv/y as given by UNSCEAR 2000UNSCEAR (2000. Th average value (0.16 Bq•L −1 ) is almost matched with Saudi Arabia (Alseroury et al, 2018), higher than Jordan (Al-Shboul et al, 2017) and lower than other countries. The present results show that the average of 40 K concentration is nearly matching the value of Nigeria (Ajayi & Owolabi, 2007), higher than Yemen (Abdurabu et al, 2016) and Jordan (Al-Shboul et al, 2017), while it is lower than the other observed values.…”
Section: Lifetime Risk Assessment (R)mentioning
confidence: 73%
“…For this reason, the metals and natural radioactivity concentration in water have been studied by many investigators in several countries (Ali et al, 2016;Radulescu et al, 2017;Ghaderpoori et al, 2018;Parhoudeh et al, 2019). In Saudi Arabia, there are limited studies on drinking water (Al-Ghamdi, 2014;Al-Zahrani, 2016;Althoyaib & El-Taher, 2016;Alseroury et al, 2018). According to our literature survey conducted by the researcher, there are no data found on the quality of schools' drinking water supplies in the city of Jeddah.…”
mentioning
confidence: 89%
“…Ra, and its shortlived daughter products [29][30][31][32][33][34][35]. The spectra of different samples were measured by a highresolution gamma-ray spectrometer (high-purity germanium (HPGe) detector).…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…These elements are found at trace levels in most exposed and unexposed ground formations. These natural radioactivity elements could dissolve in groundwater with different concentrations due to the Rock/water interactions [7]. Numerous studies have attempted to explain how to determine the natural radioactivity concentrations in groundwater [8][9][10].…”
Section: Introductionmentioning
confidence: 99%